Rapid thermal-acid hydrolysis of spiramycin by silicotungstic acid under microwave irradiation. (June 2019) - Chen, Zheng; Dou, Xiaomin; Zhang, Yu; Yang, Min; Wei, Dongbin
Abstract: Spiramycin is a widely used macrolide antibiotic and exists at high concentration in production wastewater. A thermal-acid hydrolytic pretreatment using silicotungstic acid (STA) under microwave (MW) irradiation was suggested to mitigate spiramycin from production wastewater. Positive correlations were observed between STA dosage, MW power, interaction time and the hydrolytic removal efficiencies, and an integrative equation was generalized quantitively. Rapid and complete removal 100 mg/L of spiramycin was achieved after 8 min of reaction with 1.0 g/L of STA under 200 W of MW irradiation, comparing to 30.1% by MW irradiation or 15.9% by STA alone. The synergetic effects of STA and MW irradiation were originated from the dissociated-proton catalysis by STA and the dipolar rotation heating effect of MW. STA performed much better than the mineral acid H2 SO4 under MW, due to the much stronger Brönsted acidity and higher Hammett acidity. After 8 min, 98.0% of antibacterial potency was also reduced. The m/z 558.8614 fragment (P1) and m/z 448.1323 fragment (P2) were identified as the primary products, which were formed by breaking glucosidic bonds and losing mycarose and forosamine for P1 and further mycaminose moiety for P2. Finally, production wastewater with 433 mg/L of spiramycin was effectively treated using this thermal-acid hydrolytic method. Spiramycin and its antibacterial potency both dropped to 0 after 6 min. The potency drop was supposed from the losing of mycarose and/or forosamine. To decrease both the concentration of spiramycin and its antibacterial potency, combinedly using STA and MW was suggested in this work to break down the structural bonds of the functional groups rather than to destroy the whole antibiotic molecules. It is promising for pretreating spiramycin-contained production wastewater to mitigate both the antibiotic and its antibacterial potency. Graphical abstract: Image 1 Highlights: STA and MW were combinedly used for thermal-acid hydrolytic removal of spiramycin. Synergetic effect observed was due to proton catalysis and dipolar rotation heating. Under MW irradiation, STA performed much better than mineral acid H2 SO4 . Breaking glucosidic bonds in deoxyhexoses sugars led to antibacterial potency drop. Spiramycin-contained production wastewater was successfully treated by STA and MW. Abstract : Combined using silicotungstic acid and microwave were effective in breaking glucosidic bonds of spiramycin, which led to the concentration decay and antibacterial potency mitigation.